Interaction of nucleoside diphosphate kinase B with heterotrimeric G protein beta gamma dimers: consequences on G protein activation and stability - Wieland, Thomas (Naunyn-Schmiedeberg's archives of pharmacology, 2007)
It is generally accepted that G protein coupled receptors (GPCR) activate heterotrimeric G proteins by inducing a GDP/GTP exchange at the G protein alpha subunit. In addition, the transfer of high energetic phosphate by nucleoside diphosphate kinase (NDPK) and/or the beta subunit of G proteins (G beta) can induce G protein activation. Recent evidence suggests that the NDPK isoform B (NDPK B) forms a complex with G beta gamma dimers. In this complex, NDPK B acts as a protein histidine kinase phosphorylating G beta at histidine residue 266 (His266). The high energetic phosphoamidate bond on His266 allows for a phosphate transfer specifically onto GDP and thus local formation of GTP, which binds to and thereby activates the respective G protein alpha subunit. Apparently, this process occurs independent of the classical GPCR-induced GDP/GTP exchange at least for members of the G(s) and G(i) subfamilies of heterotrimeric G proteins. By using a mutant of G beta(1) in which His266 was replaced by Leu, it was recently demonstrated that NDPK B/G beta gamma-mediated G(s) activation contributes by about 50% to basal cAMP formation and contractility in rat cardiac myocytes. Besides its apparent role in G protein activation, the complex formation of NDPK B with G beta gamma dimers might be essential for G protein stability. Depletion of either the NDPK B orthologue or G beta(1) isoforms in zebrafish embryos led to a similar phenotype displaying contractile dysfunction in the heart accompanied by a complete loss of heterotrimeric G protein expression. In conclusion, the interaction of NDKP B with G beta gamma dimers might play an important role in signal transduction, and alterations in this novel pathway might be of pathophysiological importance.